Unilateral Melanoma-Associated Retinopathy Case Report - Reinout Peeters; Freya Peeters; Julie Jacob; Dafina Draganova; Ingele Casteels; Koen Poesen; Irina Balikova (Case Reports in Ophthalmology, 2023)
In this report, we present a case of unilateral melanoma-associated retinopathy in a 72-year-old woman. The patient’s main symptoms were decreased vision and positive dysphotopsia. Unilateral electronegative electroretinogram (ERG) was suggestive for melanoma retinopathy. PET-CT discovered metastatic disease, 3 years after the initial melanoma. A prompt treatment with corticosteroids was started, followed by immunotherapy. The central and peripheral vision of the patient improved, and the ERG showed normalization of the responses. This case highlights the importance of early recognition and individualized treatment strategies for melanoma-associated retinopathy.